IMPLEMENTASI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKANHASIL BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR DI PEKANBARU - Witri, Gustimal (Jurnal Pendidikan Guru, 2017)
This research is based on the low learning result of Mathematics of third grade students of Elementary School, with the average of class 59. While the value of Minimum Exhaustiveness Criteria (KKM) of Mathematics is 73. Among the 26 students only 7 students reach KKM with classical completeness 26.92%. This research is a Classroom Action Research (PTK) conducted aimed to improve the learning outcomes of Mathematics students class III SD Pekanbaru by implementing the approach of Indonesian Realistic Mathematics Education (PMRI). The data collected in this research are observation sheet of teacher activity and student activity and learning result. The average of mathematics learning result obtained by students before action 59 increased to 69,63 in cycle I with increasing percentage 26,92%. In the second cycle increased to 83.35 with a percentage increase of 19.70%. Teacher activity in the first cycle of the first meeting obtained a score of 16 (61.54%) with sufficient category and at the second meeting obtained a score of 19 (73.08%) with sufficient category. While on the second cycle of the first meeting obtained score of 21 (80.77%) with good category and the second meeting scored 14 (92.31%) with very good category. The increase of student activity on first cycle of first meeting get score 14 (53,85%) with enough category and at second meeting get score 18 (69,23%) with enough category. While in cycle II the first meeting scores obtained are 23 (88.46%) with good category and the second meeting obtained a score of 25 (96.15%) with very good category. The result of the research in the third grade of SD Pekanbaru proves that by implementing the approach of Indonesian Realistic Mathematics Education (PMRI) can improve students mathematics learning outcomes.